Global burden, inequality, and frontier gaps of autism spectrum disorder disability in adolescents and young adults, 1990–2021: a systematic analysis of the GBD 2021 study - Lin, Derong; Shi, Zhuangtang; Hao, Zhen; Xie, Xiaohua; Fang, Jingya; Li, Mei; Zhang, Weiqing; Luo, Shuxiong; Xue, Aiguo (Frontiers in Public Health, 2025)
BackgroundAutism spectrum disorder (ASD) ranks among the leading causes of years lived with disability in adolescence and young adulthood (AYA), yet global assessments still focus on childhood and seldom examine how national development modifies burden.MethodsWe analysed Global Burden of Disease 2021 data for 204 countries and territories from 1990 to 2021. Among AYA aged 15–39 years, we extracted the age-standardised prevalence rate (ASPR) and disability-adjusted life-year rate (ASDR), stratified by sex, five-year age groups and Sociodemographic Index (SDI) quintile. Temporal trends were evaluated using the Estimated Annual Percentage Change (EAPC). Cross-country absolute and relative inequalities were quantified with the Slope Index of Inequality (SII) and Concentration Index (CIX). A half-normal stochastic frontier model defined the minimum attainable ASDR for each SDI level; country-year gaps were calculated as observed minus frontier values.ResultsFrom 1990 to 2021, prevalent ASD cases increased from 17.52 to 24.13 million and DALYs from 3.30 to 4.55 million. Despite higher counts, global age-standardised rates changed little: in 2021 the ASPR was 811.67 per 100000 (95% UI 683.34–952.87) and ASDR 153.00 (95% UI 103.77–215.64); EAPCs were near zero. Males contributed about two-thirds of the burden (rate ratio ≈2.1). Disability rose most at ages 30–39 (+56%). A persistent SDI gradient was observed: high-SDI settings recorded ASPR 1090.72 and ASDR 205.00 versus 845.15 and 158.57 in low-SDI settings. In 2021, SII was 22.53 (95% UI 12.53–32.53) and CIX 0.04 (95% UI 0.02–0.05). Several high-income economies exceeded the frontier, while Bangladesh, Somalia and Niger lay on or below it—likely reflecting surveillance gaps rather than low burden.ConclusionAbsolute ASD disability in AYA has risen mainly from population growth and case detection, not higher per capita risk. A sustained male predominance, a renewed peak at ages 30–39, and minimal progress on inequality show that economic gains alone have not reduced burden. Expanding adult screening, vocational support and community-based interventions, alongside stronger surveillance and parent training in low-SDI settings, is required to narrow global gaps.